Archaeometallurgical studies in China: some recent developments and challenging issues. (April 2015) - Mei, Jianjun; Wang, Pu; Chen, Kunlong; Wang, Lu; Wang, Yingchen; Liu, Yaxiong
Abstract: On the basis of a review of major research achievements over the past ten years, this paper discusses some challenging issues in current studies of ancient Chinese metallurgy, with a focus on the beginnings of bronze metallurgy in China, regional bronze technologies during the Shang dynasty, early developments of iron technology, emergence of lost-wax casting technology, manufacturing techniques of gold objects, and Qin metallurgy. It will also offer some observations on future directions for the study of ancient Chinese metallurgy. Highlights: An overview of major recent research on ancient Chinese metallurgy. Discussions of some challenging issues in current studies. Some observations on early East–West metallurgical connections. Future directions for the study of ancient Chinese metallurgy.